Implementing a Caring Environment Through Social Emotional Learning (Sel) Course for Student with Diverse Ability at Bilingual School - Hidayatut Thomaroh; Maslathif Dwi Purnomo (Universitas Islam Negeri Palopo, 2026)
The shift toward holistic education has drawn increasing attention to students' social and emotional well-being alongside academic achievement, particularly for students with diverse abilities learning in a second language. This study examines how the implementation of a Social Emotional Learning (SEL) course contributes to creating a caring learning environment for students with diverse abilities at a bilingual school in North Sumatra, focusing on the benefits of the course for students and how teachers support its implementation. A qualitative design was employed, involving two female SEL teachers selected through purposive sampling based on their direct responsibility for teaching the course. Data were collected through an open-ended questionnaire and analyzed using the qualitative descriptive model of Miles, Huberman, and Saldaña, comprising data reduction, data display, and conclusion drawing, with trustworthiness established through credibility, dependability, conformability, and transferability. The findings show that the SEL course fostered students' emotional regulation and social openness, increased confidence in English communication, illustrated by a documented case of a previously hesitant student, and cultivated emotional expression and language development as interconnected outcomes. Teacher support was reflected in dedicated SEL time and voluntary routines, instructional strategies integrating language practice, differentiated approaches for students with diverse abilities, responsiveness to emotional needs, and advocacy for further institutional training. Interpreted through Krashen's Affective Filter Hypothesis and Noddings' concept of the caring relation, these findings suggest that a caring environment emerges when teachers consistently treat students' emotional and linguistic needs as interconnected. The study is limited to two teachers in a single bilingual school and relies solely on self-reported data; future research involving multiple schools and student voices is recommended.